2023
DOI: 10.1523/jneurosci.0016-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Early-Life Stress-Sensitive Neuronal Ensembles Contributes to Lifelong Stress Hypersensitivity

Abstract: Early-life stress (ELS) is one of the strongest lifetime risk factors for depression, anxiety, suicide, and other psychiatric disorders, particularly after facing additional stressful events later in life. Human and animal studies demonstrate that ELS sensitizes individuals to subsequent stress. However, the neurobiological basis of such stress sensitization remains largely unexplored. We hypothesized that ELS-induced stress sensitization would be detectable at the level of neuronal ensembles, such that cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 85 publications
1
14
0
Order By: Relevance
“…Both male and female samples were collected from each group at each age. For both Std and ELS groups, approximately 10% of nuclei in the NAc were tagged and captured ( Figure 1E ), consistent with previous count estimates of experience-activated cells by immunohistochemistry (Balouek et al, 2023). We then performed ATAC-sequencing (assay for transposase-accessible chromatin; (Buenrostro et al, 2013) in both tagged and untagged cell populations to characterize and compare open chromatin regions across treatment conditions and cell populations ( Supplemental Table 1 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Both male and female samples were collected from each group at each age. For both Std and ELS groups, approximately 10% of nuclei in the NAc were tagged and captured ( Figure 1E ), consistent with previous count estimates of experience-activated cells by immunohistochemistry (Balouek et al, 2023). We then performed ATAC-sequencing (assay for transposase-accessible chromatin; (Buenrostro et al, 2013) in both tagged and untagged cell populations to characterize and compare open chromatin regions across treatment conditions and cell populations ( Supplemental Table 1 ).…”
Section: Resultssupporting
confidence: 88%
“…Given previous findings that ELS-activated cells in the NAc are preferentially reactivated by stress (Balouek et al, 2023), we examined chromatin profiles in ELS-activated and non-activated cell populations separately. To permanently tag and isolate these separate cell populations, we utilized double transgenic ArcCreER T2 x Sun1-sfGFP-Myc mice (Figure 1A) in which transgene expression is both neuronal activity-and ligand-dependent (Denny et al, 2014;Balouek et al, 2023). ELS occurred in a stress sensitive window from postnatal day P10-17 as previously described (Peña et al, 2017(Peña et al, , 2019a.…”
Section: Tagging and Capturing Stress-responsive And Non-responsive C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Early life stress (ELS) affects healthy development and aging as well as susceptibility to psychiatric disorders in humans [1][2][3][4] . Studies in humans and animals suggest ELS may increase risk for psychiatric diseases such as depression by inducing hypersensitivity to future stress exposure [5][6][7][8] . However, mechanism by which ELS sensitizes responses to future stress responses in adulthood remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal separation, a well-established model of early-life stress, has been extensively studied to investigate the long-term consequences of adverse early life events during this critical period of brain function and behaviour (Taylor et al, 2010;Korosi et al, 2012). Stress due to maternal separation (MS) in rodents leads to anxiety-like behaviours in adulthood as characterized by heightened fear, avoidance, and stress sensitivity (Banqueri et al, 2017;Lundberg et al, 2020;Balouek et al, 2023). The ventral hippocampus, a key brain area affected by MS (Dimatelis et al, 2014;Marais et al, 2009), has been shown to regulate emotions (Jimenez et al, 2018;H.…”
Section: Introductionmentioning
confidence: 99%